Women’s Double Burden in the Family: An Analysis of Reciprocal Relations Based on Mubādalah Theory in Central Lampung Regency - Ismail Hasan (Journal of Islamic Mubadalah, 2025)
This study is situated within the growing prevalence of the double burden borne by married women in Rumbia District, Central Lampung, as they are required to manage domestic responsibilities while simultaneously engaging in family-based economic activities. The article seeks to elucidate the concrete forms of this double burden, the factors that generate it, and its implications for fairness within spousal relations. In addition, the study interprets empirical findings through the lens of the mubadalah perspective. From a theoretical standpoint, the analysis integrates gender justice theory, the concept of the double burden, and the mubadalah approach within Islamic family law. Methodologically, the research employed a qualitative case study design, involving women engaged in dual roles, their husbands, and local community figures as informants. Data were collected through in-depth interviews, participant observation, and document analysis. The findings indicate that the division of domestic labor remains markedly unequal, spousal and familial support tends to be limited, and women experience heightened physical and psychological strain, despite their efforts to develop various coping strategies. Viewed through the mubadalah framework, these practices appear to be inconsistent with the principle of reciprocity. Consequently, the study recommends strengthening mubadalah-based education within families, grassroots religious forums, and local policy initiatives that promote a more equitable and reciprocal division of labor.